A case of near-hanging - Mahajan, Kunal; Tyagi, Arun; Waran, Marcia; Srivastava, Awani K (Indian Journal of Case Reports, 2019)
Hanging is the suspension of a person by a noose or ligature around the neck and has been a common method of capital punishmentsince medieval times. Hanging is also a common method of suicide/homicide worldwide as also in India. We report a case ofattempted suicidal hanging admitted in our intensive care unit. The patient, a 32-year old male, presented with poor clinical status,in gasping condition, hypoxemic and required immediate intubation, resuscitation, assisted ventilation and intensive care treatment.He received standard supportive intensive care and made a full clinical recovery without any neurological deficit. The purpose of thecase report is to emphasize that the cases of near-hanging need to be aggressively resuscitated and managed irrespective of dismalinitial presentation.